Dampak Covid-19 Terhadap Pelaksanaan Pembelajaran Daring pada Kelas Rendah di Sekolah Dasar - Husni Mubarok; Hammatul Aliyah; Ahmad Wildan Faza (Jurnal Ilmiah Tarbiyah Umat, 2022)
This study was conducted with the aim of knowing the impact of the Covid-19 on daring classroom learning in elementary schools. The research used is a qualitative research that is a literature study (Study of Literature Research). Data collection techniques using documentation techniques, namely collecting relevant theoretical studies and references sourced from scientific literature in journals. Retrieval of information sources from selected articles and news, namely those found with the impact of covid-19 and learning from low grades in elementary schools. As a result, 12 sources were obtained, then the most relevant were selected and 5 articles and 3 news items were selected. The results in this study indicate that the impact of covid-19 on courageous learning for lower classes in elementary schools, namely learning methods carried out remotely with the help of technology make students need to adapt to face online learning systems and have an impact on students' learning comprehension. . Intensive collaboration and communication is needed between teachers, parents and students so that online learning can be carried out effectively.